Decarbonization of Isolated Power Systems through the Use of PV, BESS, and Hydrogen - Andrian, Ricky Cahya; Habibi, Muhamad (Jurnal Ar Ro'is Mandalika (Armada), 2025)
The isolated electrical system on Gili Ketapang Island, East Java, which is entirely dependent on a diesel power plant (Installed Capacity: 2x525 kW), faces four pressing issues: (1) High Production Cost (BPP) due to 100% dependence on imported fuel oil (BBM), (2) Risk of power deficit and N-1 failure after adding 144 kVA customers, (3) Significant CO2 emissions, and (4) Extreme fuel supply logistics risk, involving five manual stages and prone to marine pollution. This case study aims to design a phased dedieselization strategy to transform the Gili Ketapang PLTD into a 100% green, reliable, and zero-emission energy system. The proposed solution is the implementation of a PV-BESS -Hydrogen hybrid system through three stages: Stage 1: 170 kW/800 kWh Battery Energy Storage System (BESS) for peak shaving and efficiency optimization; Stage 2: Integration of Hydrogen Fuel Cells to substitute fuel and verify safe H2 logistics; and Stage 3: Full integration of PV-BESS-Hydrogen to completely eliminate fuel. The urgent recommendation is to accelerate the installation of BESS to immediately address the potential power deficit of 88 kW (night peak load of 558 kW) and optimize the operation of existing engines, making it a green mini-grid model that is ready for replication.